Asynchronous vs Synchronous: Effects of Online Learning on Students' Oral Presentation Skills - Indriyani, Vivi; Jasmienti; Fendi, Hasri (Journal of Education Technology, 2024)
Online learning has become popular globally in every field of education as a result of advances in information and communication technology despite the COVID-19 pandemic. Online learning can be done synchronously and asynchronously. Based on this explanation, the purpose of this study was to analyze and compare synchronous and asynchronous online learning on students' oral presentation skills. This research method is an experiment with a quasi-experimental design. Two classes were selected as the sample for this study using a purposive sampling technique. With the provisions of one class as experimental class 1 by treating students with asynchronous online learning, while the experimental class 2 learning is carried out synchronously online. The research instrument used was a performance test, in which students made oral presentations. Analysis of research data using SPSS with the stages of normality test, homogeneity test, and t test. The results of the study showed that there was a difference in the average student learning outcomes, namely oral presentation skills and synchronous and asynchronous online learning processes. Based on the average difference, it shows that students are better at making oral presentations when learning is carried out asynchronously. Based on the results of this research, it can be concluded that online learning can be used as an alternative for the learning process, especially asynchronously, especially in relation to oral presentations.